Head and neck second primary cancer rates in the human papillomavirus era: A population‐based analysis. (6th August 2015) - Diaz, Dayssy Alexandra; Reis, Isildinha M.; Weed, Donald T.; Elsayyad, Nagy; Samuels, Michael; Abramowitz, Matthew C.
Abstract: Background: Patients with head and neck cancer are at high risk for second primary malignancies. Human papillomavirus (HPV)‐driven tumors are generally high‐grade oropharyngeal cancers. We analyzed the incidence of second primary malignancy of the head and neck in patients with primary squamous cell carcinoma (SCC) of the head and neck and temporal trends in the HPV era. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was queried for patients with SCC of the head and neck (range, 1973–2008). Cumulative incidence rates of second primary malignancy of the head and neck were compared based on competing risk analysis. Results: A total of 104, 639 cases were included in this study, of which 4616 patients had second primary malignancy of the head and neck. Oropharyngeal cancer incidence increased over time. Estimated incidence rate/10, 000 person‐years (105.5, 80.6, and 50.2 for 1973–1989, 1990–1999, and 2000–2008, respectively) and cumulative incidence rates (10‐year rates of 6.68%, 5.72%, and 4.59% for 1973–1989, 1990–1999, and 2000–2008, respectively) of second primary malignancies of the head and neck for patients with oropharyngeal cancer decreased over time ( p < .001). The second primary malignancy of the head and neck incidence rate was significantly lower in patients with high‐grade oropharyngeal cancer from 2000 to 2008 (30.3 vs 65.5 and 54.6 from 1973–1989 and 1990–1999, respectively; p < .001). Conclusion: The incidence of second primary malignancy of the head and neck in patients with head and neck cancer has decreased over time. This is driven by lower rates in patients with high‐grade oropharyngeal cancer, is temporally related with increases in HPV‐associated oropharyngeal cancer, and suggests that incidence rates of second primary malignancy of the head and neck may be lower for HPV‐associated cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E873–E883, 2016